Neonatal Birth Fractures - Tyler C. McDonald, MD; C. Lake Higdon, BS; William A. Cutchen, MD (Journal of the Pediatric Orthopaedic Society of North America)
Fractures in newborn infants due to trauma imparted by the birthing process are rare. These skeletal injuries can occur in the form of diaphyseal fractures or, much less commonly, separation of physes. Often, prompt recognition of birth fractures is difficult, which may lead to late presentation. Careful and thorough physical examination can identify the presence of these injuries, leading to appropriate treatment. Diaphyseal fractures can be treated non-operatively with light immobilization and comfort measures, with an excellent prognosis. Physeal injuries more often require surgical treatment to stabilize the displaced epiphyseal fragment after restoring anatomy. This review is designed for the orthopaedic clinician as an overview of the most commonly encountered varieties of these rare birth fractures so that they may be better equipped to recognize, diagnose, and offer appropriate treatment. Key Concepts: (1) Fractures and physeal separations sustained from birth trauma are rare and often require a high index of suspicion for diagnosis. (2) The overwhelming majority of diaphyseal fractures sustained from birth trauma can be treated nonoperatively with an excellent prognosis. (3) Physeal separations can be easily confused with other diagnoses, such as joint dislocations, and more often require surgical intervention for stabilization.